2022
DOI: 10.1177/0734242x221123490
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the collection and composition of plastic waste in the digital waste bank and the reduction of potential leakage into the ocean

Abstract: Most ocean plastic pollution results from leakage from waste management activities on land, mainly in coastline communities. In this research, the digitalization of waste management will be evaluated to improve the prevention of leakage. The digitalization means introducing mobile apps into the waste bank that can improve waste management efficiency while providing reliable data. The data on waste management were gained from Griya Luhu App which has been used in 13 villages around Gianyar, while the waste gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Utilizing the integrated sustainable waste management (ISWM) framework [15,16], this study addresses a noted gap identified by Filho et al, who mentioned the lack of studies specifically examining integrated urban waste management in developing countries [17]. Previous studies have often focused on individual actors in municipal solid waste (MSW) management, such as the informal sector [10,18], waste banks [19,20], private waste management companies [21], and governance [8,22]. However, the roles of current multi-stakeholder actors in plastic waste collection in Indonesia have not yet been clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing the integrated sustainable waste management (ISWM) framework [15,16], this study addresses a noted gap identified by Filho et al, who mentioned the lack of studies specifically examining integrated urban waste management in developing countries [17]. Previous studies have often focused on individual actors in municipal solid waste (MSW) management, such as the informal sector [10,18], waste banks [19,20], private waste management companies [21], and governance [8,22]. However, the roles of current multi-stakeholder actors in plastic waste collection in Indonesia have not yet been clearly defined.…”
Section: Introductionmentioning
confidence: 99%